Hopf Algebras. - Radford, David E. (World Scientific, 2011)
The book provides a detailed account of basic coalgebra and Hopf algebra theory with emphasis on Hopf algebras which are pointed, semisimple, quasitriangular, or are of certain other quantum groups. It is intended to be a graduate text as well as a research monograph.
10.3 Integrals and semisimplicity.
Keywords: Hopf algebras.; Algèbres de Hopf.; MATHEMATICS -- Algebra -- Linear.; Hopf algebras